Lightyear [videorecording (DVD)] - MacLane, Angus; Headley, Jason, 1973-; Aldrich, Matthew (Screenwriter); Lasky, Jeremy; Megibben, Ian; Giacchino, Michael (Disney/Pixar, 2022)
Discover the story of the man behind the toy as the legendary Space Ranger goes on an intergalactic adventure and gets stranded with only ambitious -- but untrained -- recruits and his robot companion cat.